Captain Kidd - Bogeaus, Benedict; Lee, Rowland V.; Digiview Productions ([Place of publication not identified] Digiview Productions, 2004)
Set in the seventeenth century, Captain Kidd convinces unwitting King William III to allow him to act as protector of a valuable treasure ship, little realizing that Kidd has designs of his own on the very cargo he as been assigned to safeguard. This rousing adventure, filled with great action sequences and spectacular sea battles is sure to please. Adding a touch of romance to the proceedings are the enigmatic Randolph Scott and glamorous Barbara Britton.
Original story by Robert N. Lee
Screenplay by Norman Reilly Raine
Charles Laughton, Randolph Scott, Barbara Britton, Reginald Owen, John Carradine, Gilbert Roland, John Qualen, Sheldon Leonard, William Farnum, Henry Daniell, Reginald Owen, Abner Biberman.
DVD ; Standard full frame ; Stereo sound.
In English.
Keywords: Pirates -- Great Britain -- Drama; Drama; Romance